Information Technology and Organizational Agility - Hassan, Noor Hafizah; Arshad, Noreen Izza (Journal of Applied Technology and Innovation, 2019)
This paper provides a review of the literature while contributing to academic understanding of the concepts of organizational agility and Information Technology Infrastructure Flexibility. The research identiﬁed fifty articles from total nine databases and e-resources. The paper identified focus on Malaysian organizations especially automobile industry. The ﬁndings in this paper will help academics to gain a better understanding and to develop the concepts on organization agility with the help of IT infrastructure flexibility as a driver. Realizing Information Technology and human as important assets of organization. Evolving on how to manage these critical assets effectively in enhancing organizational performance. Correspondingly towards achieving optimum competitive advantage and sustaining the longevity in the industry.